Upaya Meningkatkan Hasil Belajar Bernyanyi Unisono Siswa Menggunakan Metode Discovery Learning Di Kelas VII.1 SMPN 2 Padangsidimpuan - Ermawati Ermawati; Jagar Lumbantoruan (SENDRATASIK UNP, 2022)
This research is classified as Class Action Research (CAR). The data analysis technique carried out is the result of applying the actions taken, namely collecting data as needed, classifying data according to its parts, clarifying data, namely checking for data errors to get accurate data, and then analyzing and concluding the data. The results showed that there was an increase in the learning outcomes of singing in a unison with the discovery learning method in class VII.1 student of SMP Negeri 2 Padangsidimpuan. The improvement of student learning can be seen in the quality of the process shown through the enthusiasm and activeness of students when participating in music learning. Improvements in the quality of results can be seen from the increase in scores and average scores before and after the implementation of the action. The average value of the initial ability of students is 44.12. In the first cycle, the average value increased to 71.66 and in the second cycle, it increased significantly to 88.33. The increase in the average score from pre-action to cycle II, increased by 44.21% and has met the Minimum Graduation Completeness (KKM) of 75. From the results of the research above, it is known that the discovery learning method has succeeded in increasing student learning outcomes in singing local folk songs. in-class VII.1 SMP Negeri 2 Padangsidimpuan.